2006
DOI: 10.1152/ajpcell.00593.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain induces cell proliferation through calcium-dependent phosphorylation of Akt (protein kinase B) in opossum kidney proximal tubule cells

Abstract: Cardiotonic glycosides, like ouabain, inhibit Na(+)-K(+)-ATPase. Recent evidence suggests that low molar concentrations of ouabain alter cell growth. Studies were conducted to examine the effect of ouabain on Akt phosphorylation and rate of cell proliferation in opossum kidney (OK) proximal tubule cells. Cells exposed to 10 nM ouabain displayed increased Akt Ser(473) phosphorylation, as evidenced by an increase in phospho-Akt Ser(473) band density. Ouabain-stimulated Akt Ser(473) phosphorylation was inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 51 publications
2
59
0
3
Order By: Relevance
“…Subsequently, Lee & Klaus (1971) and Cohen et al (1976) described similar effects of digitalis and its derivatives on the sodium pump. We (Khundmiri et al 2006(Khundmiri et al , 2007 and others (Bluschke et al 1976, Gao et al 2002, Ferrari 2010) have demonstrated that low concentrations of cardiotonic steroids increase Na C /K C ATPase-mediated ion transport in renal proximal tubule cells. As early as 1914, Douglas Cow discovered microcirculation between kidneys and adrenal glands (Cow 1914), which would indicate that EO synthesized in the adrenal glands could directly affect the sodium reabsorption in the kidneys without reaching the systemic circulation.…”
Section: Atpase Activitymentioning
confidence: 69%
See 2 more Smart Citations
“…Subsequently, Lee & Klaus (1971) and Cohen et al (1976) described similar effects of digitalis and its derivatives on the sodium pump. We (Khundmiri et al 2006(Khundmiri et al , 2007 and others (Bluschke et al 1976, Gao et al 2002, Ferrari 2010) have demonstrated that low concentrations of cardiotonic steroids increase Na C /K C ATPase-mediated ion transport in renal proximal tubule cells. As early as 1914, Douglas Cow discovered microcirculation between kidneys and adrenal glands (Cow 1914), which would indicate that EO synthesized in the adrenal glands could directly affect the sodium reabsorption in the kidneys without reaching the systemic circulation.…”
Section: Atpase Activitymentioning
confidence: 69%
“…The laboratory of Zijian Xie made an important discovery by demonstrating that a population of non-ion-transporting and highaffinity Na C /K C ATPase resides in caveolae, forming a signaling complex with Src kinase (Pierre & Xie 2006). When cardiotonic steroids at low picomolar to nanomolar concentrations bind to Na C /K C ATPase in the caveolae, this activates Src, which in turn results in transactivation of EGFR and activation of the PI3K-Akt pathway, the Ras-Raf-ERK MAP kinase pathway, IP3R activation, and calcium oscillations, resulting in regulation of earlyresponse genes associated with cell growth, motility, and metabolic pathways (Peng et al 1996, Kometiani et al 1998, Contreras et al 1999, Aizman et al 2001, Abramowitz et al 2003, Dmitrieva & Doris 2003, Dong et al 2004, Khundmiri et al 2006, Liu & Askari 2006, Liu et al 2007a,b, 2011, Pierre et al 2008, Quintas et al 2010, Morrill et al 2012, Bai et al 2013, Wu et al 2013, Rincon-Heredia et al 2014.…”
Section: Namentioning
confidence: 99%
See 1 more Smart Citation
“…Unpublished observations from Dr. Alexander Chibalin and coworkers show that A-769662 can inhibit the Na ϩ -K ϩ -ATPase (personal communication). In addition, it has been shown in some (11,21,29,30,50) but not all models (23,24) that inhibition of the Na ϩ -K ϩ -ATPase by ouabain increases PI3-kinase activity, possibly through an association between p85 and the ␣ 1 -subunit of the Na ϩ -K ϩ -ATPase, leading to increased Akt phosphorylation. This effect can be inhibited by wortmannin (30).…”
mentioning
confidence: 99%
“…One concern is that the circulating levels of CTS seen in pathological conditions do not appear to cause extensive inhibition of the pump in vitro and in vivo (Bagrov, Shapiro et al 2009). In fact, the growth regulatory effects of CTS are seen even at nano and sub-nano molar concentrations, which do not cause any demonstrable inhibition of the pump activity (Aydemir-Koksoy, Abramowitz et al 2001;Aydemir-Koksoy and Allen 2001;Saunders and Scheiner-Bobis 2004;Khundmiri, Metzler et al 2006;Qiu, Gao et al 2007). Another concern is that it has been difficult if not impossible to demonstrate changes in cytosolic sodium caused by physiological and even pharmacological concentrations of CTS.…”
Section: Signaling Though the Sodium Pumpmentioning
confidence: 99%